The importance of the International Tennis Federation's junior boys' circuit in the development of professional tennis players - Reid, M.; Crespo, M.; Santilli, L.; Miley, D.; Dimmock, J. (Journal of Sports Sciences, 2007)
The relationship between junior boys' tennis success, as measured by a top 20 International Tennis Federation's Junior Circuit (ITFJC) ranking, and subsequent ranking accomplishments in professional men's tennis is discussed. The names, countries, and birthdates of all players to achieve a top 20 ITFJC boys' year-end ranking from 1992 to 1998 were recorded. The progress of these players through the professional ranks was then tracked to the end of 2004. Results indicate that 91% of top 20-ranked boys achieved a professional men's ranking, while a stepwise regression analysis revealed junior ranking (JR) to be a predictor of future, professional ranking ( = 0.232, r2 = 0.054, p < 0.05). A regression equation [predicted professional rank = 78.17 + 6.31*(JR)] accounted for a significant amount of variance in professional ranking. For male players, therefore, the achievement of a top 20 junior ranking appears to be a reasonable yardstick for future, professional success. The type of surface upon which junior players develop their games was also shown to influence professional ranking highs, with play on clay courts or a combination of clay and hard courts helping to produce higher, professionally ranked players than hard court play alone (p 0.01).